THE EFFECT OF USING ANDROID APPLICATION IN TEACHING PRONUNCIATION - Kayyis, Rahmatika -; Tristiana, Novita Eka; -, Hardono - (STKIP Muhammadiyah Pringsewu, 2019)
The research aim was to know the effect of English Pronunciation: Speak/ Pronounce English? toward the students? pronunciation. This study is pre-experimental design. The sample was 35 students from English for Nurse 1 class of STIKes Aisyah Pringsewu. Instrument used to test the competencies is using 126 words from the minimal pairs poem entitled ?English is Tough Stuff?. It had progress based on the data that the ? ? of correct words in pretest, 40.35, it is increasing in post-test, ? ? 116. It is suggested that the application should be developed into the type that brings various benefit. Keywords: Articulation, Application, Technology